Simulation of tidal hydrodynamics in Sabang Bay, Indonesia. (December 2018) - Setiawan, I; Alfawirsa, M A; Haditiar, Y; Rizal, S
Abstract: Tidal hydrodynamics of currents and sea level in Sabang Bay are simulated by a one-dimensional numerical model. We generate the dynamics by using the amplitude and tidal components of Hamburg direct data Assimilation Methods for TIDEs (HAMTIDE) in the open boundary. HAMTIDE is a model data obtained from the tidal inverse method. The tidal simulation is based on several harmonic constants of M2, K1, K2, S2, O1, and N2. Simulations of the combined harmonic constants are run over a 30 day period and verified by the measurement data of the Hydrography and Oceanography Center, Indonesian Navy. The verification results indicate that the numerical sea level model is quite good, with the correlation coefficient r = 0.81.